2003
DOI: 10.1002/masy.200350939
|View full text |Cite
|
Sign up to set email alerts
|

Copolyesters based on poly(butylene terephthalate)s containing cyclohexyl groups: synthesis, structure and crystallization

Abstract: Poly(butylene terephthalate‐co‐cyclohexylene dimethylene terephthalate) copolymers PBTCT, were synthesized by melt condensation with compositions ranging from 94/08 to 23/77. 13C NMR spectroscopy was used to study the microstructure of the copolyesters and was found to be completely random. The melting temperature, crystallization temperature on cooling, enthalpy of melting and crystallization followed an eutectic behaviour. Thermal and x‐ray diffraction studies indicated that the copolyesters in all compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…1 The ring structure of 1,4 cyclohexanedimethanol (CHDM) at room temperature flips from the e,etrans cyclohexylene ring to form an a,a-trans cyclohexylene ring via a twisted-boat structure. 6,[12][13][14] Sivaram et al 15 have resolved the high processing temperature problem by synthesizing a random copolyester of PCT and poly(butylene terephthalate) (PBT). 1,[3][4][5] However, one problem lies with its rigid structure, which gives rise to a high melting temperature (T m ) (278-318°C) compared to other conventional polyesters (PET: 250°C and PBT: 225°C).…”
Section: Introductionmentioning
confidence: 99%
“…1 The ring structure of 1,4 cyclohexanedimethanol (CHDM) at room temperature flips from the e,etrans cyclohexylene ring to form an a,a-trans cyclohexylene ring via a twisted-boat structure. 6,[12][13][14] Sivaram et al 15 have resolved the high processing temperature problem by synthesizing a random copolyester of PCT and poly(butylene terephthalate) (PBT). 1,[3][4][5] However, one problem lies with its rigid structure, which gives rise to a high melting temperature (T m ) (278-318°C) compared to other conventional polyesters (PET: 250°C and PBT: 225°C).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the synthesis of PCT-based copolymers or reactive blending with other polyesters have been studied to improve their processibility as well as thermal and mechanical properties through variation of the copolymer composition. [7][8][9][10][11] It is well-known that, in most copolyesters where both A and B components are crystallizable, the degree of crystallinity decreases with increasing the composition of minor component, and as a result the copolymers often become totally amorphous even at low comonomer content. If two crystallizable components of the copolymers are compatible in their crystal lattices (i.e., cocrystallization), thermal and mechanical properties of the copolymers can be controlled without significant loss of crystalline properties.…”
Section: Introductionmentioning
confidence: 99%
“…If two crystallizable components of the copolymers are compatible in their crystal lattices (i.e., cocrystallization), thermal and mechanical properties of the copolymers can be controlled without significant loss of crystalline properties. [10][11][12][13][14][15] Yoo et al 9 reported that poly(1,4-cyclohexylenedimethylene terephthalate-co-ethylene terephthalate) copolymers, in which ethylene terephthalate (ET) units can crystallize with complete rejection of 1,4-cyclohexyleneterephthalate (CT) units from the crystal whereas CT units can cocrystallize with ET units to some extent, exhibits cocrystallization. However, copolymers with the middle range of comonomer content are completely amorphous.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in order to improve certain properties of these polymers numerous modifications of their chemical structure have been proposed: copolymerization, blending with other polymers, and use of additives. In particular, recently there has been great interest in exploring the effects of the introduction of 1,4‐cyclohexylene rings into the polyester chains 2–11. The cycloaliphatic units can partially or totally substitute the aromatic groups or the aliphatic moieties, causing important variations in the properties of the starting materials.…”
Section: Introductionmentioning
confidence: 99%